Effect of turmeric extract (Curcuma longa) on apoptosis in a rat model of mammary adenocarcinoma with adriamycin-cyclophosphamide chemotherapy - Dwi Purbo Rahayu; Selamat Budijitno; Neni Susilaningsih (Plant Trends, 2025)
Breast cancer is one of the most common life-threatening diseases and being a leading cause of women death globally, while chemotherapy can elicit adverse effects and treatment resistance. Curcumin is an active compound found in turmeric (Curcuma longa) that has promising anticancer activity. The aim of this study was to investigate the effect of turmeric on caspase-3 expression and the apoptosis index of mice with mammary adenocarcinoma receiving Adriamycin-Cyclophosphamide chemotherapy. The study subjects were using female Balb/c mice and were divided into five treatment groups: i) a negative control group, ii) a group with Adriamycin-Cyclophosphamide chemotherapy, and three groups treated with a combination of Adriamycin-Cyclophosphamide chemotherapy; and iii) Curcuma longa extract at doses of 100 mg/kgBW, iv) 150 mg/kgBW, and v) 200 mg/kgBW. Immunohistochemical staining was used to assess Caspase-3 expression, and apoptosis was evaluated using TUNEL staining. The turmeric extract groups demonstrated a significantly higher expression of caspase-3 and apoptosis than that of the control groups (p = 0.045 and p = 0.009, respectively). This result indicates the potential of curcumin to act in synergy with chemotherapy by enhancing apoptosis at lower doses and with fewer side effects. To sum up, turmeric extract can enhance the expression of caspase-3 and the apoptotic index in breast cancer cell lines treated with Adriamycin-Cyclophosphamide chemotherapy. [Plant Trends 2025; 3(2.000): 33-40]